Ketersediaan Jalur Hijau sebagai Ruang Terbuka Hijau di Koridor Pendidikan Kota Bandarlampung (Studi Kasus: Jalan Za Pagar Alam) - Rein Susinda Hesty; Maulidya Paramitha; Muttaqin Al Hafizh (Universitas Batanghari Jambi, 2022)
Green open space (RTH) is one of the important elements of the city and can be accessed by the community, which functions as ecological, socio-cultural, architectural, and economic. Physically, green open space (RTH) can be divided into natural green open space in the form of natural wild habitats, protected areas, and national parks, as well as non-natural or built green open spaces such as parks, sports fields, cemeteries, or green roads. In the green open space, there are plants that grow and are useful, among which there are different types of plants planted, namely tree plants, shrubs, vines, and herbal plants. One of the functions of tree vegetation in Green Open Space (RTH) is to help absorb GHG emissions. This study aims to identify the characteristics of vegetation in the education corridor on Jalan ZA Pagar Alam Bandarlampung and identify vegetation absorption in the education corridor on Jalan ZA Pagar Alam Bandarlampung to see the availability of green lanes as green open space in the Education Area Corridor at Jalan ZA Pagar Alam Bandarlampung. In this case, data collection was carried out through primary data collection with observation collection techniques to determine the characteristics and amount of tree vegetation, and the analysis carried out was descriptive quantitative with the calculation of the central tendency, namely the mean and mode. Based on the results of the analysis, the education corridor on Jalan ZA Pagar Alam has the availability of 782 individual tree vegetation with 31 tree vegetation characteristics, and the most abundant tree vegetation characteristics are Pometia pinnata or matoa trees. The characteristics of the existing trees have their respective uptake capabilities. In the education corridor, Jalan ZA Pagar Alam has an absorption capacity of 37.66 tons/day or 1,129.79 tons/month or 13,557.46 tons/year from 782 individual trees with different characteristics. which has the largest absorption, namely palm trees, with an absorption capacity of 27.41 tons/day, or 822.31 tons/month, or 9,867 tons/year.